Synthesis, Antioxidant, Analgesic, Anti-Inflammatory Activities and Molecular Docking Studies of Newly 1,2,4-Triazole-3-yl-sulfanyl-acetamide Derivatives - Hotta, Santanu Kumar; Rout, Sudhanshu Sekhar; Kumar, Anjan; Panigrahi, Ghanshyam; Chiranjeevi, P. (Asian Journal of Chemistry, 2026)
A series of ten 1,2,4-triazole-3-yl-sulfanyl-acetamide derivatives bearing a mercapto (-SH) group were synthesized and characterized using FTIR, 1H NMR, 13C NMR, UV, mass spectrometry and DSC. The compounds were prepared within two structural frameworks: (i) N-(p-toluoyl)-[4-phenyl-5-(pyridin-4-yl)-4H-1,2,4-triazol-3-yl]sulfanylacetamide and (ii) N-[4-(1-oxo-3-phenyl-propenyl)phenyl]-2-(4-phenyl-5-pyridin-4-yl-4H-1,2,4-triazol-3-ylsulfanyl)acetamide. Molecular docking against COX-2 (PDB ID: 5F1A) highlighted compound 4a from framework I (binding energy -12.09 kcal mol–1) and compound 5e from framework II (binding energy -13.15 kcal mol–1) as the most promising compounds with favourable interactions, supporting their potential as lead molecules for further biological evaluation. In addition, physico-chemical, pharmacokinetic and HOMO-LUMO (ΔEH-L = 9.985 and 9.986 eV) also suggested that 4a and 5e are two lead candidates with positive drug-ability profiles (0.60 and 0.68). Prior to selecting safe/non-toxic doses of both leads for biological activity, the acute oral toxicity was investigated following the OECD-423 guidelines, where 200 and 400 mg/kg were selected as non-toxic doses for in vivo biological activity. The analgesic activity of the lead compounds 4a and 5e was evaluated in Wistar albino rats using the Eddy’s hot plate method. Anti-inflammatory effects were investigated through both in vitro protein denaturation assays (employing hot and cold-water extracts) and the in vivo carrageenan-induced paw edema model. The antioxidant potential of 4a and 5e was evaluated using the DPPH radical scavenging assay. Structural variation from the simple aryl scaffold of 4a to the chalcone framework of 5e provided insight into the structure–activity relationship. The ortho-hydroxy substituent in 5e enhanced radical-scavenging capacity and may contribute to its activity against oxidative stress, pain and inflammation. In silico, in vitro and in vivo findings identified 4a and 5e as promising derivatives with favourable analgesic, anti-inflammatory, antioxidant and drug-likeness profiles.